2016
DOI: 10.1002/ejoc.201501584
|View full text |Cite
|
Sign up to set email alerts
|

Multichannel Reaction of α‐Bromo­enones with 1,2‐Diamines: Synthesis of 1,4‐Diazabicyclo[4.1.0]hept‐4‐enes by Reaction with N‐Unsubstituted 1,2‐Diamines

Abstract: The reaction of 2‐bromoenones with N‐unsubstituted 1,2‐diamines was studied. An easy access to 1,4‐diazabicyclo[4.1.0]hept‐4‐enes was developed. The multistep mechanism of the reaction is discussed. Final conclusions on the influence of the structure of the starting 2‐bromoenones and 1,2‐diamines on the direction of the reaction are established.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 45 publications
1
6
0
Order By: Relevance
“…It is very important that the reaction of ketones 1 with amino alcohols 2 is highly stereoselective: in the NMR spectra of the products 3 and 5 there is only one set of signals. Previously, we have observed the same high stereoselectivity in the formation of piperazines from diamines and bromoenones 1 , , …”
Section: Resultssupporting
confidence: 65%
See 1 more Smart Citation
“…It is very important that the reaction of ketones 1 with amino alcohols 2 is highly stereoselective: in the NMR spectra of the products 3 and 5 there is only one set of signals. Previously, we have observed the same high stereoselectivity in the formation of piperazines from diamines and bromoenones 1 , , …”
Section: Resultssupporting
confidence: 65%
“…We have also shown that the unusual 1,2‐migration of the trifluoromethyl group completed a cascade of transformations of CF 3 ‐bromoenones with symmetrically substituted ethylenediamines leading to a very rare type of piperazine derivatives . The reaction of the same bromoenones with N , N′ ‐unsubstituted 1,2‐diamines selectively gave 3,6‐diaza‐bicyclo[4.1.0]hept‐2‐enes . Finally, fluorinated α‐bromoenones react smoothly with β‐mercapto alcohols to give 1,4‐oxathianes in moderate yields; amino alcohols containing a primary amino group give morpholines and/or 1,4‐oxazepanes ― a previously unknown heterocyclic system ― in good to excellent yields and often with very high stereoselectivity .…”
Section: Introductionmentioning
confidence: 99%
“…Diamines bearing two primary amino groups react with bromoenones in other ways. In all cases these reactions represent extremely short routes to mono‐ or bis‐aziridine derivatives, (Scheme ).…”
Section: Reactions With Nucleophilesmentioning
confidence: 99%
“…The most efficient approach, however, for the construction of such heterocyclic systems employs fluorinated building blocks. For example, we have recently demonstrated that fluorinated bromoenones can be used for the assembly of trifluoromethylated piperazinones, bicyclic piperazines, morpholines, oxazepanes, and other heterocycles …”
Section: Introductionmentioning
confidence: 99%